Professional Development of EFL Teachers at the Department of English and Literature, Batna 2 University: Challenges and Opportunities - Mouas, Samia (جامعة باتنة, 2021)
يتزايد الاهتمام الأكاديمي بالتطوير المهني للمعلمين في جميع أنحاء العالم لسبب بسيط هو أن تحقيق الجودة في التعليم يعتمد إلى حد كبير على جودة تعليم المعلمين في المجتمع. يضاف إلى ذلك أن جائحة 19-COVID قد غيرت عملية التدريس بشكل كبير مع ظهور التعلم / التدريس الإلكتروني. استخدمت الدراسة الحالية استبيانا عبر الإنترنت مصمما في نماذج Google Forms وتم إرساله إلى إجمالي عدد المعلمين (العدد = 61) عبر رسائل البريد الإلكتروني المهنية الخاصة بهم. أظهرت النتائج أنه على الرغم من أن المشاركين في هذه الدراسة لا يزالون يحملون فكرة التطوير المهني التقليدية، فإن 94.9% من العينة يشاركون الرأي حول ضرورة تطويره لتحسين معارفهم ومهاراتهم. شارك 19 معلما من أصل 39 في أنشطة التطوير المهني. ومع ذلك، لم يلق توجيه المعلمين الأقل خبرة وتوجيههم الاهتمام المطلوب. يمكن لنتائج هذه الدراسة إعلام المعلمين وواضعي السياسات بأهمية التطوير المهني في تحسين جودة المعلمين وتحسين مهارات التعلم لدى الطلاب. نأمل أن يساعد هذا الاتجاه المستقبلي لبرامج التطوير المهني، خاصة لمعلمي اللغة الإنجليزية كلغة أجنبية في الجزائر. Academic interest in professional development (PD) of teachers throughout the world is growing as the achievement of quality in education depends to a large extent upon the quality of the teachers in society. Moreover, the COVID-19 pandemic has changed the process of teaching with the rise of e-Learning/Teaching. This study used a questionnaire and a semi-structured interview to EFL teachers in the department of English and Literature at Batna 2 University to gather information about their PD challenges and opportunities. Results show that although the respondents still hold the idea of traditional PD, 94.9% of them share the view of the necessity of PD to improve their knowledge and skills; however, mentoring and guiding less experienced teachers did not receive the attention required. Findings of this study can inform educators and policymakers of the importance of PD in enhancing teacher quality and improving students’ learning skills to help the future direction of PD programs for EFL teachers in Algeria.
Keywords: تأهيل المعلمين -- جودة التعليم -- التدريس الإلكتروني -- الجامعات الجزائرية